2021
DOI: 10.1530/ec-21-0223
|View full text |Cite
|
Sign up to set email alerts
|

Association of central obesity and high body mass index with function and cognition in older adults

Abstract: Objective: To investigate the association of normal body mass index (BMI) with central obesity (CO), high BMI with CO, high BMI without CO, and normal BMI without CO, with function and cognition in older adults. Methods: Cross-sectional study involving 754 participants ≥ 65 years. Data collected include demographics, cognition and physical measurements. Results: Females had higher prevalence of high BMI with CO and lower prevalence of high BMI without CO than males (61.0% vs. 44.6% and 4.6% vs. 15.0% respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This is termed the "obesity paradox" and most studies used BMI to define obesity which may not differentiate between fat mass and fat free mass (49). A recently published study on BMI and waist circumference showed that high BMI was associated with better functional and cognitive status especially in males (15). Males in our study had significantly higher FFMI and highest tertile of FFMI group had significantly higher MoCA scores.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This is termed the "obesity paradox" and most studies used BMI to define obesity which may not differentiate between fat mass and fat free mass (49). A recently published study on BMI and waist circumference showed that high BMI was associated with better functional and cognitive status especially in males (15). Males in our study had significantly higher FFMI and highest tertile of FFMI group had significantly higher MoCA scores.…”
Section: Discussionmentioning
confidence: 55%
“…BMI need to be interpreted with caution in older adults as loss of physiological height may lead to over-interpretation and lack of correlation with percentage body fat, distribution, or body composition (8)(9)(10)(11). Unlike younger adults, high BMI in older adults is associated with better function, cognition, and survival (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, BMI is often used as an anthropometric indicator to measure nutritional status (Lai et al., 2020), and researchers (Merchant, Kit, et al., 2021;Merchant, Seetharaman, et al., 2021) believe that low BMI (BMI < 18.5 kg/m 2 ) is more correlated with increased mortality in the older adults. This study found that 55.5% of participants had a BMI in the normal range (18.5–23.9 kg/m 2 ), 36.4% of older adults were overweight or obese and only 8.1% were underweight, with a BMI of less than 18.5, reflecting malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…High BMI may be a protective factor in older adults especially those at risk of declining functional status and indeed has been associated with improved survivability in older adults ( 54 ). Body composition is also an important factor, as men in the high BMI group but without central obesity performed better on the functional and cognitive tests ( 55 ).…”
Section: Discussionmentioning
confidence: 99%